Solid state electrochemical and calorimetric study of the equilibrium phase (Cu, Ag)2S. (March 2016) - Tesfaye, Fiseha; Lindberg, Daniel; Taskinen, Pekka
Graphical abstract: Thermodynamic properties of the superionic solid solution (Cu, Ag)2 S and stromeyerite, including Δf G ° values, have been investigated. For the first time, Δtr/melt H ° values of the ternary phases have been determined experimentally. Highlights: Reproducible galvanic cells of different electrolytes were measured accurately. Δf G ° values for the solid solution (Cu, Ag)2 S and stromeyerite have been determined. T tr/melt along the composition Ag0.92 Cu1.08 S have been determined by DSC method. New enthalpies of phase transitions and melting of (Cu, Ag)2 S have been determined. Abstract: Thermodynamic stabilities of the solid solution (Cu, Ag)2 S in equilibrium with (Cu + S)-compounds have been studied by an EMF method, using the fast Ag + ion conducting solid electrolytes. In addition to providing data for experimental reproducibility check, the usage of two different electrolytes, in their respective ionic conduction domains, allowed EMF measurements in the (Ag + Cu + S) system over a wide temperature range. For the first time, EMF values for the solid solution (Cu, Ag)2 S have been measured above T = 500 K. The EMF measurements were made with the solid state electrochemical cells of the type Pt(−) |Ag| Ag + ion conductor |(Ag + Cu + S)-phase assemblage | Pt(+), within the temperature range from (383 to 578) K. Phase transition thermodynamic properties of stromeyerite (Ag0.93 Cu1.07 S) and the solid solution (Cu, Ag)2 S have been studied by the differential scanning calorimetry (DSC) technique. Based on the measured E vs. T relations, thermodynamic functions of the Cu-rich solid solution (Cu, Ag)2 S have been determined. Accurate thermodynamic properties of the solid solution including data in a new temperature range have been obtained. The results obtained with calorimetric measurements were analyzed and, for the first time, enthalpies of phase transitions and fusion of the solid solution (Cu, Ag)2 S have been experimentally determined.